Economic policy uncertainty and cryptocurrencies: A country-level wavelet analysis - Almeida, J.; Gonçalves, T. C. (Journal of Alternative Investments, 2024)
This article employs a wavelet-based methodology to analyze and characterize the relationships between cryptocurrencies and country-specific economic policy uncertainty (EPU). The authors analyze these relationships over the different stages of the COVID pandemic (pre-COVID, COVID, and post-COVID), and across various investment frequencies. Their results show that the cryptomarket does not function as a hedge or safe haven against economic policy uncertainty at the country level. Moreover, they find these relationships to be dynamic, evolving across specific time periods. Notably, during the COVID-19 pandemic, there was an increase in relationships, indicating the pandemic’s impact on market dynamics. Their analysis highlights the prevalence of these relationships at short-term investment horizons, noting the significant participation of retail investors actively involved in high-frequency trading. Lastly, the findings strongly align with the adaptive market hypothesis (AMH), emphasizing that investor behavior is subject to behavioral biases, and rationality is not always evident.